Evaluation of the humoral immune responses of brucellosis vaccine (Rev.1) in sheep: A study from Iran - J. Gharekhani; E. Barati; M. Dadar (Bulgarian Journal of Veterinary Medicine)
The live strain of Brucella melitensis Rev1 is recognised as the available vaccine for controlling brucellosis in small ruminants. This study aimed to assess the humoral immune responses in sheep when administered the native Rev.1 vaccine. All animals were inoculated with the Rev.1 vaccine, and blood samples were collected on days 0, 14, 28, 44, 55, and 69 post-vaccination. These samples were tested using the modified Rose Bengal plate test (mRBPT), Wright test, 2-mercaptoethanol (2-ME) test, and enzyme-linked immunosorbent assay (ELISA) techniques. After six rounds of sampling, all animals tested negative in the mRBPT evaluation, and the control group exhibited low levels of anti-bodies to brucellosis when using ELISA. In the test group, most cases of positive mRBPT results were observed on days 14 and 28 of sampling. The Wright, 2-ME, and ELISA tests revealed that the highest antibody levels were detected 14 days after vaccination. In contrast to the Wright and 2-ME findings, the level of antibodies continued to rise until the 44th day after vaccination when using ELISA. The results demonstrated the stimulation of humoral immune responses in the target animals through the native vaccine, which could be employed to immunise livestock in endemic areas like Iran. The ELISA test proved to be more effective than conventional tests in revealing the serological response induced by Rev.1 vaccination, although ELISA may not reliably distinguish between anti-bodies generated by the vaccine and those resulting from the disease.